Proceedings of the 28th International Conference on Computational Linguistics 2020
DOI: 10.18653/v1/2020.coling-main.86
|View full text |Cite
|
Sign up to set email alerts
|

Answering Legal Questions by Learning Neural Attentive Text Representation

Abstract: Text representation plays a vital role in retrieval-based question answering, especially in the legal domain where documents are usually long and complicated. The better the question and the legal documents are represented, the more accurate they are matched. In this paper, we focus on the task of answering legal questions at the article level. Given a legal question, the goal is to retrieve all the correct and valid legal articles, that can be used as the basic to answer the question. We present a retrieval-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…During our research on deep learning architectures, we found very simple architectures like SCNN [44], which have a small number of parameters that can still outperform other models. Interestingly, we also found the simple combination of CNN [35] architecture and attention mechanism [33] can give better results than bulky models in some specific cases. This chapter will answer the question of under what conditions can the end-to-end model perform well in a legal text processing task.…”
Section: Dissertation Outlinementioning
confidence: 75%
See 1 more Smart Citation
“…During our research on deep learning architectures, we found very simple architectures like SCNN [44], which have a small number of parameters that can still outperform other models. Interestingly, we also found the simple combination of CNN [35] architecture and attention mechanism [33] can give better results than bulky models in some specific cases. This chapter will answer the question of under what conditions can the end-to-end model perform well in a legal text processing task.…”
Section: Dissertation Outlinementioning
confidence: 75%
“…With the development of the internet and the explosion of digital data, methods of using machine learning [6,51], especially deep learning [20,59,33], are becoming more and more popular in NLP in general and automated legal processing in particular. Catering to this trend, a variety of datasets [68,25,19,72,36] and tasks [1,15,69,9] are introduced.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Binary Classification. Between the two U.S. datasets, although the Congressional bill survival prediction dataset [106] has a large number of samples, we selected Overruling [112] 1.1K French EU Y Retrieve related law articles for legal questions GerDaLIR [24] 123K German EU Y Precedent case search Kien et al [113] 5.9K Vietnamese VT N Retrieve related law articles for legal questions * Available upon request and/or under terms 1 https://casetext.com/blog/a-benchmark/ 2 https://www.sec.gov/ 3 https://sites.google.com/view/aila-2021/task-2-summarization-of-legal-judgements 4 https://sites.ualberta.ca/~rabelo/COLIEE2021/ [14] because the underlying task (deciding whether a given sentence overturns a precedent) could have more significant real-world impact. From the EU datasets, we chose Terms of Service rather than the ECHR dataset (cases from the European Court of Human Rights) [37] because we used two other datasets of court cases among the remaining tasks.…”
Section: A Dataset Selectionmentioning
confidence: 99%
“…Among the latest published works in this family of methods, we can highlight the following: The Neural Attentive Text Representation from (Kien et al, 2020), the introduction of Few-shot Learning in the legal domain (Wu et al, 2020). Novel techniques for language modeling (Huang et al, 2020b).…”
Section: Ontology-based Solutionsmentioning
confidence: 99%